PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI DAN MOTIVASI TERHADAP PERILAKU EKSTRA PERAN PEGAWAI DI DITKERSINHAN - Muhammad Kasim Lamazi; Mochammad Subagio (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2022)
Abstract :The purpose of this study was to determine the Effect of Leadership Style, Competence, and Motivation on Organization Citizenship Behaviour at the Ministry of Defense of the Republic of Indonesia. The number of samples in this study was 90 people who were employees of the Ministry of the Defense Republic of Indonesia Ditkersinhan. The data analysis technique used is descriptive statistics and multiple linear regression analysis.The measurement in this study was carried out by giving the value of each item statement of all variables using a Likert scale. Data from the questionnaire were analyzed including data description, testing of research requirements, including normality test, homogeneity test, and linearity test. To prove the effect of variables on this study using data analysis techniques with path analysis.The conclusions of the results of this study are: partially Leadership Style has a direct positive effect on Organization Citizenship Behaviour, meaning that if the Leadership Style increases, it causes an increase in Organization Citizenship Behaviour. Competence has a direct positive effect on Organization Citizenship Behaviour meaning that if high Competency causes an increase in Organization Citizenship Behaviour. Motivation has a direct positive effect on the Organization Citizenship Behaviour, meaning that when Motivation increases cause an increase in Organization Citizenship Behaviour. Competence has a direct positive effect on motivation, meaning that if competency increases it causes better motivation. Leadership style has a direct positive effect on employee competence, meaning that good leadership leads to an increase in employee competency.Keywords : Leadership Style, Competence, Motivation and Organization Citizenship Behaviour.